1994
DOI: 10.1111/j.1365-2249.1994.tb07014.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in subset distribution, activation, and differentiation of T ceils isolated from large intestine biopsies in HIV infection

Abstract: Intestinal T cells have a unique state of activation and differentiation which might specifically affect or be affected by HIV infection. Lymphocyte subsets in the peripheral blood are well characterized, but our knowledge about intestinal lymphocytes in HIV infection is incomplete. We therefore analysed lymphocytes isolated from large intestine biopsies of AIDS patients and controls by three-colour cytofluorometry. In the large intestine of HIV-infected patients CD4 T cells were reduced and CD8 T cells were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 29 publications
2
12
1
Order By: Relevance
“…CD103 expression was high in the cervix, consistent with its mucosal nature. We did not find changes in CD103 expression in HIV-infected patients, unlike Schneider et al, 23 who found decreased CD103 expression on intestinal CD8 T cells, although not on CD4 cells, of HIV-infected patients. The fact that our data were based on all CD3 cells may explain this difference.…”
Section: Discussioncontrasting
confidence: 98%
“…CD103 expression was high in the cervix, consistent with its mucosal nature. We did not find changes in CD103 expression in HIV-infected patients, unlike Schneider et al, 23 who found decreased CD103 expression on intestinal CD8 T cells, although not on CD4 cells, of HIV-infected patients. The fact that our data were based on all CD3 cells may explain this difference.…”
Section: Discussioncontrasting
confidence: 98%
“…It is not unlikely that the classification of Tregs by an arbitrary cut-off point for the definition of CD25 high cells could result in diverse findings, since CD25 expression is not restricted to regulatory CD4 ϩ cells. 22,36 Moreover, low CD4 ϩ T-cell numbers can make it extremely difficult to set the cut-off for the CD25 high cell population.…”
Section: Discussionmentioning
confidence: 99%
“…22 Biopsies were washed once in 20 mL NaCl 0.9% to remove adherent blood and mucus and cut into small fragments. Fragments were preincubated overnight at 4°C in 50 mL RPMI 1640 medium (Gibco, Karlsruhe, Germany) containing 10% fetal calf serum (FCS), 100 U/mL penicillin, 100 g/mL streptomycin, 50 g/mL gentamycin, 2.5 g/mL amphotericin, 25 mM HEPES buffer (all from Seromed Biochrom, Berlin, Germany), 0.05 M 2-mercaptoethanol (Gibco), 0.01% collagenase (CLS III; Seromed Biochrom), 0.01% trypsin inhibitor (type I-S; Sigma-Aldrich, Steinheim, Germany), and 0.01% DNAse (DNAse I from bovine pancreas; Hoffmann-La Roche, Basel, Switzerland) and then incubated for 4 hours (37°C) in a humid chamber (5% CO 2 ).…”
Section: Isolation Of Lamina Propria Mononuclear Cellsmentioning
confidence: 99%
“…Although there are methodologic constraints in this approach, including variation in the exact site of biopsy or resection and the small area of colon assessed in both the HIV-infected (median ϭ 0.99/mm 2 ) and control samples (median ϭ 1.54/mm 2 ), our results were consistent with those of others which suggest an overall increase in CD8 ϩ T-cell numbers in the gut during HIV infection. 1,3,4,32 Overall, despite the clear loss of CD161 ϩϩ /MAIT cells from blood, they are still detectable in gut, as judged by analysis of CD8 ϩ CD3 ϩ MDR1 ϩϩ cells. …”
mentioning
confidence: 99%